Spatial training in the Water Maze facilitates extinction and prevents reinstatement of cocaine-induced Conditioned Place Preference - Ávila-Gámiz, Fabiola; Mañas-Padilla, María del Carmen; Gil Rodríguez, Sara; Zambrana-Infantes, Emma; Santín-Núñez, Luis Javier; Ladrón de Guevara-Miranda, David (My University, 2021)
Manipulation of adult hippocampal neurogenesis has been shown to affect the establishment of cocaine-context associations as well as extinction learning and reinstatement of these maladaptive memories. In this work, we aimed to study whether spatial training in the Water Maze (WM) task was able to increase survival/differentiation of adult-born hippocampal neurons, thus facilitating extinction and preventing primed reinstatement of cocaine-context associations. For this purpose, 20 adult male C57BL/6J mice (12 weeks-old) were trained in the Conditioned Place Preference (CPP) paradigm with an ascending dosing schedule (2, 4, 8 and 16 mg/kg/day). Two days later, animals received systemic bromodeoxyuridine (BrdU) injections (75 mg/kg) to label new cells that proliferated after cocaine-CPP acquisition. One week later, a group of mice (n=10) was submitted to a 7-days spatial training in the WM while another group of mice (n=10) remained undisturbed at home cage. When BrdU+ new-born hippocampal cells reached maturation (~6 weeks-old), mice were tested for CPP memory retrieval. Then, animals were submitted to forced CPP extinction and tested for CPP extinction and reinstatement induced by a 2 mg/kg cocaine priming. The results showed that animals trained in the WM required fewer sessions to extinct cocaine-CPP and showed reduced reinstatement compared to the animals maintained at home cage. Therefore, our data suggest that learning in a spatial memory task is able to reduce long-term persistence of cocaine-context associations. Further analyses are required to elucidate the role of adult hippocampal neurogenesis on these beneficial effects.
Keywords: Conducta; Behaviour; Cocaine; neurogenesis; Mice